Evaluation of Correlation between Residual Ridge Resorption and Bone Density in Women Wearing Removable Complete Dentures: 1-Year Clinical Prospective Study - Brovina, Merita Shkodra; Selmani, Mimoza; Bukleta, Manushaqe Selmani (European Journal of General Dentistry, 2025)
Residual ridge resorption (RRR) is considered to be a continuous and highly complex process with a multifactorial etiology. This study aims to assess the rate of mandibular RRR in women with complete edentulism and its correlation with bone density and to investigate the effect of complete denture wearing on RRR.This randomized prospective clinical study included 60 women aged 50 to 80 years old (mean: 63.37 ± 6.32) with complete edentulism. The study groups were divided according to T-score values of DXA scan (dual-energy X-ray absorptiometry) into two groups: 30 women with low bone density osteoporosis/osteopenia and 30 women with normal bone density. The mandibular ratio index (MRI) measured on panoramic radiography (orthopantomogram [OPG]) 2D using Sidexis SG program is used to investigate the correlation of RRR with vertebral bone mineral density of L1–L4. MRI is categorized into three grades: class I ≥ 2.34; class II 1.67–2.33; and class III ≤ 1.66. Duration of complete edentulism is divided into three periods: 0–5, 5–10, >10 years. All participants received complete dentures. Measurements were evaluated before treatment and 1 year after prosthodontic treatment with complete dentures.The correlation analysis between DXA test values and MRI showed a moderately positive yet insignificant correlation, R = 0.32 (p > 0.05). For each unit increase in T-score value, MRI increases by 0.04 (B = 0.04), a nonsignificant difference at p > 0.05. Patients with edentulous period >10 years have an average of 0.01 mm (B = 0.01) resorption compared with patients with edentulous period of 1 to 10 years, nonsignificant at p > 0.05 (p = 0.97). For each year of increasing age, MRI decreases by 0.0004 mm (B = 0.0004) and is not significant at p >0.05 (p = 0.97). One year after wearing dentures, the value of MRI for Z = 2.52 and p <0.05 (p = 0.01) is significantly higher.There is no significant correlation between osteoporosis and RRR. However, wearing dentures affects the resorption of the residual ridge. Age and duration of edentulism do not have a significant impact on RRR.
Keywords: mandibula; residual ridge resorption; bone density; complete dentures